Extracts of Coreopsis tinctoria Nutt. Flower Exhibit Antidiabetic Effects via the Inhibition of α-Glucosidase Activity - Wujie Cai; Lijing Yu; Yu Zhang; Li Feng; Siyuan Kong; Hongsheng Tan; Hongxi Xu; Cheng Huang (Journal of Diabetes Research)
The aim of this study was to assay the effects of Coreopsis tinctoria Nutt. flower extracts on hyperglycemia of diet-induced obese mice and the underlying mechanisms. Coreopsis tinctoria flower was extracted with ethanol and water, respectively. The total phenol, flavonoid levels, and the constituents of the extracts were measured. For the animal experiments, C57BL/6 mice were fed with a chow diet, high-fat diet, or high-fat diet mixed with 0.4% (w/w) water and ethanol extracts of Coreopsis tinctoria flower for 8 weeks. The inhibitory effects of the extracts on α-glucosidase activity and the antioxidant properties were assayed in vitro. We found that the extracts blocked the increase of fasting blood glucose, serum triglyceride (TG), insulin, leptin, and liver lipid levels and prevented the development of glucose tolerance impairment and insulin resistance in the C57BL/6 mice induced by a high-fat diet. The extracts inhibited α-glycosidase activity and increased oxidant activity in vitro. In conclusion, Coreopsis tinctoria flower extracts may ameliorate high-fat diet-induced hyperglycemia and insulin resistance. The underling mechanism may be via the inhibition of α-glucosidase activity. Our data indicate that Coreopsis tinctoria flower could be used as a beverage supplement and a potential source of drugs for treatment of diabetics.